Fuzzy Neural Networks Controller for a Chaotic Nonlinear Gyro Using Sliding-Mode Surfaces - Seyed Alireza, Mohseni; Seyed Mohammadreza, Mohseni (2008)
In this paper a decoupled sliding-mode with fuzzy neural networks controller for a chaotic nonlinear system is presented. The fuzzy neural network (FNN) is the main regulator controller, which is used to approximate an ideal computational controller. Using Lyapunov law, we derive the decoupled sliding-mode control law and the related parameters adaptive law of FNN. Using this approach, the response of system will converge faster than that of previous reports.